Determinants of low birth weight among newborns delivered at Mettu Karl comprehensive specialized hospital, southwest Ethiopia: a case–control study - Samuel Ejeta Chibsa; Mustafa Adem Hussen; Kenbon Bayisa; Bilisumamulifna Tefera Kefeni (Scientific Reports, 2024)
Abstract Low birth weight is a newborn delivered with birth weight of less than 2500 g regardless of gestational age is called. It is a significant issue affecting over 30 million infants worldwide. Thus, the study determine factors associated with low birth weight among newborns delivered at Mettu Karl Comprehensive Specialized Hospital, Southwest Ethiopia. A facility-based case–control study was conducted with 336 newborns (112 cases and 224 controls) from September 12 to December 23, 2022. The study population was newborns with birth weights of 2500 g to 4000 g as controls and newborns with birth weights < 2500 g were cases. Simple random sampling techniques were used to recruit study participants with a ratio of 1 to 3 cases to controls, respectively. Data was collected by interviews and a checklist. Data were entered and analysed using SPSS version 23. Binary and multivariate logistic regression analyses were computed to identify factors associated with low birth weight, a p-value less than 0.05 was used to declare the strength of statistical significance. A total of 327 newborns were contacted, yielding a 97% response rate. MUAC < 23 cm (AOR = 2.72, 95% CI 1.24 to 6.19), inadequate diet diversification (AOR = 4.19, 95% CI 2.04 to 8.60), lack of iron and folic acid supplementation (AOR = 2.94, 95% CI 1.25 to 6.88), history of hypertension (AOR = 2.55, 95% CI 1.09 to 6.00), and lack of nutritional counselling (AOR = 4.63, 95% CI 2.22 to 9.64) were determinants of low birth weight. Low birth weight is linked to residence, maternal MUAC, hypertension history, and ANC visit. Lifestyle modifications, early detection, management, and nutrition information can reduce risk.